Contribution of oriented structure and rigid nanofillers to mechanical enhancement of die-drawn PP/MWCNT composites. (January 2020) - Wu, Pingping; Luo, Xiehuai; Zhang, Tongying; Yang, Qi
Abstract: Oriented structure, mainly controlled by processing conditions, is another efficient method of reinforcing polymer materials in addition to compounding with rigid inorganic fillers such as carbon nanotubes (CNTs). The mechanical properties of oriented polypropylene (PP)/multiwalled CNT (MWCNT) composites, which are vital to their application fields, are investigated extensively in this paper, with an aim to distinguish the contribution of MWCNTs contents from that of the oriented structure to the final performance of the composite. The results indicate that MWCNTs mainly increase the modulus of the composites by approximately 140%. The oriented structure formed during the die-drawing process contributes more to the enhancement of tensile strength, increasing up to 550%. The modulus and tensile strength can be further improved by increasing the drawing speed. Moreover, the tensile stress field in the die-drawing process can vastly improve the dispersion of the MWCNTs in the matrix, thus providing a new idea for improving the dispersion of nanofillers in the polymer matrix. Highlights: Die-drawing process contributes more to increase tensile strength. MWCNTs mainly increase modulus rather than tensile strength. Tensile strength and modulus can be further improved by increasing the drawing rate. The die-drawing process can vastly improve the dispersion of MWCNTs in the PP matrix. MWCNTs can hinder the molecular chain orientation.